Ethnobotanical research under the COVID-19 pandemic: assessing a remote method for documenting Indigenous plant-related knowledge - Holt, Anne Marie; Bredero zur Lage, Robin; Gomes, Adrian; Serke, Anna; Louis, Elizabeth; Louis, Nita; Gomes, Konaukii; Suttie, Irene; Louis, Vincent; Rybka, Konrad; van Andel, Tinde (Ethnobotany Research and Applications, 2023)
Background: In response to the limitations on fieldwork imposed by the COVID-19 pandemic, we describe and assess a remote method for documenting plant-related knowledge, using smartphones that requires no in-person interaction between an on-site Indigenous community and off-site researchers. Methods: The on-site team identified the Indigenous taxa, created equivalents of photo vouchers, and recorded their names and uses as voice messages using a smartphone, thereby learning about plants from one another. They then sent the data using WhatsApp messages to the off-site team, who identified the botanical names of the taxa, and analyzed the plant-related knowledge. Results: We assess the remote, collaborative, and transdisciplinary quality of the method, factoring in communication, audiovisual documentation, species identification, knowledge exchange, logistics, and ethics. Despite the problems we experienced with identifying taxa growing in high forest and translation issues that complicated the documentation of plant uses, the method was on the whole a success. It allowed the on-site team to activate their passive knowledge of their language and share their knowledge with their relatives. The off-site team identified 57% of the recorded 54 taxa to species level and documented their names and uses as primary audio data, which keep on enhancing the quality of the documentation. Conclusions: Smartphones can be used as research tools during periods of restricted physical access, but also to extend research beyond the fleeting field visits and to elevate the empirical standard of ethnobotany when it comes to language data. We see such remote research solutions not as replacements for in-person collaborations, but as valid and dynamically evolving research methods in their own right. Keywords: smartphones, empiricism, photo vouchers, Taruma, Wapichan, Guyana